Blockchain, crypto and DeFi bridging finance and technology - Di Maggio, Marco 1985- (Ascent Audio, 2025)
Step into the realm of blockchain and cryptocurrency like never before with Blockchain, Crypto and DeFi: Bridging Finance and Technology. Crafted by Marco Di Maggio, not just a Harvard professor of finance but an esteemed advisor to giants like Coinbase, this is your roadmap from foundational theories to cutting-edge applications. This is far from an academic discourse detached from reality; it seamlessly integrates theory with practice through detailed case studies and practical coding tutorials. Navigating the digital landscape today demands more than just passing familiarity with the latest technologies. Delving deep into blockchain and cryptocurrencies has become a pivotal skill set for anyone looking to thrive in this constantly shifting digital era. Whether you're a student aiming for a career in finance and technology, an academic seeking to expand your knowledge base, or a professional looking to stay ahead of the curve, this textbook offers unparalleled insights into the mechanics and implications of blockchain technologies. Blockchain, Crypto and DeFi is not just a textbook but a journey into the heart of digital finance, marked by Di Maggio's engaging style and deep expertise. Accompanied by additional online resources, this book is your go-to resource and your gateway to mastering the blockchain revolution.
Online resource; title from title details screen (O'Reilly, viewed March 4, 2025)
Keywords: Blockchains (Databases); Cryptocurrencies; Chaînes de blocs; Cryptomonnaie; cryptocurrencies; Audiobooks; Livres audio